Emprendimiento agroindustrial con el aprovechamiento de zapallo (cucurbita máxima) como materia prima. - Gunsha Lamiña, Nancy Veronica (2026)
Pumpkin is a product with high nutritional value and has been used as a raw material for the production of agro-industrial products in several academic studies. This research proposes the development of an agro-industrial business venture, focusing on the commercialization of various products based on the use of pumpkin (Cucurbita maxima) as a raw material. This proposal draws on formulations and economic studies previously developed in published theses. Through a systematic review using the PRISMA method, 47 national studies related to pumpkin processing were identified. After applying inclusion criteria such as the description of processing procedures and cost analysis, 11 studies were selected. To validate the reliability of these studies, experimental verification was conducted using data from two of them, randomly selecting a beverage and a dressing made from pumpkin pulp and seeds, respectively. This comparison allowed us to determine if the economic and technical analyses were correctly formulated, as well as to verify quality and stability. The proposed business plan includes a production line of 11 products: dressing, preserves in syrup, sweet and sour sauce, pumpkin arepas, cookies, pasta, instant dessert, compote jam, energy bars, and beverages. A financial study was conducted, considering a total investment of $7,229.61. With an initial production of 45 units per product and an increase of 15 units per product per month, an initial net profit of $384.51 is projected. With monthly production increases, a final constant net profit of $1l8.24 is estimated, recovering the investment in the eighth month. Furthermore, research gaps were identified in product development, such as maltodextrin and natural colorings, which opens opportunities for future innovations.